Psoriasis and neurodegenerative diseases—a review - Nowowiejska, Julia; Baran, Anna; Flisiak, Iwona (Frontiers in Molecular Neuroscience, 2022)
Psoriasis is a chronic skin disease with underlying genetic, inflammatory and immunological background, which is a great medical problem, currently regarded as a systemic condition. Neurodegenerative diseases are characterized by a progressive loss of nervous tissue, which affect elderly people more frequently, therefore it is suspected that, due to society’s aging, morbidity is going to increase. We performed a thorough review in order to investigate for the first time whether psoriasis may predispose to different particular neurodegenerative diseases – Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). PubMed search resulted in retrieval of 833 records, of which 78 eligible were included in the review. Our thorough analysis revealed there are some potential links between psoriasis and NDs (inflammation, oxidative stress, genetics, cardiometabolic disorders) but there is no strong evidence that psoriasis may predispose to NDs. Based on the evidence, it seems that the risk of PD in psoriatics is not increased, and the evidence for increased risk of AD slightly prevails the data that state the opposite. ALS risk does not seem to be increased in psoriatics. The paucity of original studies does not allow for the formulation of definitive conclusions but encourages to perform further investigations.